The Influence of Brand Image, Brand Trust and Loyalty Program on Purchasing Intensity of Indosat (IM3) Products in Ngronggot District, Nganjuk Regency - Wijaya, Devi Nanda; Purnomo, Hery (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to determine and describe the influence of Indosat brand image, Indosat brand trust and Indosat (IM3) loyalty programs on purchasing interest in products IM3 in Ngronggot District, Nganjuk Regency. Design/Method/Approach : This study analyzes the influence of Indosat brand image, Indosat brand trust and Indosat loyalty program (IM3) on purchase interest using a causal quantitative method with subjects of Indosat provider users in Ngronggot District, a sample of 40 respondents with a non-probability sampling technique. The data analysis technique uses multiple linear regression tests, namely, among others, instrument tests, classical assumption tests, multiple linear regression tests, determination tests and hypothesis tests. Research Finding : This study shows that loyalty programs, brand trust and brand image have a positive and significant effect on purchasing interest in Indosat products (IM3). In addition, brand image, brand trust and loyalty programs together have a positive and significant effect on purchasing interest. Theoretical contribution/Originality : This study contributes to the understanding of Indosat (IM3) loyalty program, Indosat brand image and Indosat brand trust towards telecommunication product purchasing behavior in the local market. Practitionel/Policy implication : This research can provide a general overview of marketing strategies, designing loyalty programs, and understanding customer needs and expectations in encouraging sustainable purchases. Research limitation : This research only focuses on Indosat brand image, Indosat brand trust, Indosat (IM3) loyalty programs and also the intensity of consumer purchases of Indosat products.